Improved bounds for acute triangulations of convex polygons - Zamfirescu, Carol T., (Utilitas Mathematica, 2013)
We present a novel method of constructing non-obtuse and acute triangulations of planar convex n-gons,improving existing bounds presented in [L. Yuan,Discrete Comput. Geom. 34,697-706(2005)] for 6 ≤ n ≤ 11 and 6 ≤ n ≤ 56, respectively.